2006
DOI: 10.28945/3045
|View full text |Cite
|
Sign up to set email alerts
|

Task Complexity and Informing Science: A Synthesis

Abstract: Task complexity is a construct widely used in the behavioral sciences to explore and predict the relationship between task characteristics and information processing. Because the creation and use of IT in the performance of tasks is a central area of informing science (IS) research, it follows that better understanding of task complexity should be of great potential benefit to IS researchers and practitioners. Unfortunately, applying task complexity to IS is difficult because no complete, consistent definition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 91 publications
0
39
0
Order By: Relevance
“…These tasks reflect goals to be achieved or instructions to be performed (Gill and Hicks, 2006). They ideally relate to what trainees want to learn, invite them to use different skills and leave some room to decide on methods and/or activities to solve related problems (Barrack and Mount, 2013;Bartram and Roe, 2008;Eraut, 2007;Rawaswami and Dreher, 2007;Van Merriënboer and Kirschner, 2013).…”
Section: Selecting and Sequencing Tasksmentioning
confidence: 99%
See 2 more Smart Citations
“…These tasks reflect goals to be achieved or instructions to be performed (Gill and Hicks, 2006). They ideally relate to what trainees want to learn, invite them to use different skills and leave some room to decide on methods and/or activities to solve related problems (Barrack and Mount, 2013;Bartram and Roe, 2008;Eraut, 2007;Rawaswami and Dreher, 2007;Van Merriënboer and Kirschner, 2013).…”
Section: Selecting and Sequencing Tasksmentioning
confidence: 99%
“…Normally, these tasks are highly structured, familiar and of a routine nature, and thus experienced by the trainee as being not too complex. Simple tasks generally prevent cognitive overload, because little ability is sufficient to meet the task requirements (Gill and Hicks, 2006).…”
Section: Selecting and Sequencing Tasksmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of design task complexity Gill and Murphy (2011) Objective Complexity rests on three primary sources (Wood, 1989):…”
Section: Multiple Pkms Roles From Representation To Publishingmentioning
confidence: 99%
“…The initial inspiration for the series of articles being presented is a 2006 article in Informing Science titled "Task Complexity and Informing Science: A Synthesis" (Gill & Hicks, 2006). Based upon their analysis of several hundred articles that either defined or applied the task complexity construct, the authors concluded that there was no possible consensus definition.…”
Section: Introduction To Task Complexitymentioning
confidence: 99%